2006
DOI: 10.1103/physrevd.74.064001
|View full text |Cite
|
Sign up to set email alerts
|

Black holes in pure Lovelock gravities

Abstract: The Lovelock gravity is a fascinating extension of general relativity, whose action consists of the dimensionally extended Euler densities. Compared to other higher order derivative gravity theories, the Lovelock gravity is attractive since it has a lot of remarkable features such as that there are no more than second order derivatives with respect to metric in its equations of motion, and that the theory is free of ghost.Recently in the study of black string and black brane in the Lovelock gravity, a special … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
155
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(165 citation statements)
references
References 47 publications
10
155
0
Order By: Relevance
“…In analogy to what happens with Lovelock gravity, we call this case the pure quasi-topological case. In the context of Lovelock theory, this case has received attention since it's the simplest case that admits a unique constant curvature solution that also propagates a graviton [47][48][49]. The theory therefore reads 5) and the black holes solution reduces to…”
Section: Pure Quasi-topological Gravitymentioning
confidence: 99%
“…In analogy to what happens with Lovelock gravity, we call this case the pure quasi-topological case. In the context of Lovelock theory, this case has received attention since it's the simplest case that admits a unique constant curvature solution that also propagates a graviton [47][48][49]. The theory therefore reads 5) and the black holes solution reduces to…”
Section: Pure Quasi-topological Gravitymentioning
confidence: 99%
“…Since we have squared the junction condition, we must plug the solution back into (27) in order to determine the relative orientation consistent with the solution. A consistent solution will obey an even number of the three inequalities:…”
Section: Timelikementioning
confidence: 99%
“…EGB is the N = 2 case of the Lovelock polynomial. Vacuum solutions have been determined for Lovelock gravity in general [20][21][22] as well as for dimensionally continued [5,[23][24][25], and also for pure Lovelock black holes [26,27]. Sharma [28] showed that the limiting case of the polytropic fluid may be regarded as isothermal and is important in the study of clusters of stars.…”
Section: Introductionmentioning
confidence: 99%